STRATEGI BRANDING POLITIK DEWAN PIMPINAN WILAYAH PARTAI NASDEM BALI DALAM MEMBANGUN BRAND IDENTITY - Dewi, K. Ade Yulia; Pascarani, Ni Nyoman Dewi; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2018)
ABSTRAK Based on the survey results of Saiful Mujani Research and Consulting in 2016, 52 percent political parties in Indonesia got a low trust and bad judgments of society. Overcome this, the Regional Leadership Board (DPW) Partai NasDem Bali formed a political branding. The purpose of this research is to discuss the political branding strategy undertaken by DPW Partai NasDemBali in building brand identity, so as to introduce and differentiate the party with others. This research uses qualitative descriptive approach with informant determination using purposive sampling and snowball sampling technique. Data obtained through interviews, observation, and documentation. This research data analysis techniques, namely data reduction, data presentation and conclusion. The result of this research shows that the strategy of political branding conducted by DPW Partai NasDem Bali in establishing brand identity is starting with the determination of political segmentation and positioning, then using line extension strategy, brand extension and multibrand by forming political branding in the form of tagline, logo and jingle "Sing NasDem, Sing Keren". Keywords: Brand Identity, Political Branding Strategy, Political Communication, Political Marketing.